Information Content of Sustainability Reporting on Performance of Unlisted Manufacturing Firms in South Africa - PILLAY, Surendran; OBALADE, Adefemi A. (Journal of Environmental Management and Tourism, 2020)
There have been conflicting arguments on whether sustainability reporting impacts on the performance of firms. This study examined the information content of sustainability reporting on the performance of non-listed manufacturing firms in South Africa. A total of five-years of audited annual reports of 70 unlisted manufacturing firms from 2014 to 2018 were used for the study. Random effect model was selected for the estimation of panel data. The study found that lagged sustainability reporting has a positive and significant impact on both current return on assets and economic value added. The implication of these results is that firms can increase the profits and value by adopting sustainability reporting. Therefore, it is recommended that the unlisted firms in South Africa should adopt sustainability reporting as a way of boosting their public image and performance.